COMPARATIVE STUDY OF THE EFFECTIVENESS OF FINAL IRRIGATION PROTOCOLS IN SMEAR LAYER REMOVAL: A STUDY BY MEV (CIPEEX, 2025)
The study aims to compare the effectiveness of different final irrigation protocols in removing the smear layer (SL) in root canals, using Scanning Electron Microscopy (SEM) for detailed analysis. The residual layer, formed during endodontic treatment and composed of organic and inorganic fragments, can compromise treatment success if not properly removed. To achieve the objective, fifty bovine incisors were selected, which were decrowned and standardized. These teeth were divided into five groups: a control group, which did not receive final irrigation, and four experimental groups that used different combinations of chelating solutions (17% EDTA and 0.2% chitosan) and activation methods (conventional irrigation and passive ultrasonic irrigation). The effectiveness of the protocols was evaluated by MEV, which analyzed the presence of SL in different portions of the root canals. The results showed that the combination of EDTA with passive ultrasonic irrigation (PUI) was the most effective in removing SL, surpassing the other combinations tested. The cervical third of the root canals exhibited more open tubules compared to the middle and apical thirds, although there were no statistically significant differences between the middle and apical thirds. The study concludes that the EDTA + PUI protocol provides the best removal of SL, significantly improving cleaning and disinfection.
Keywords: Chelating Agents; Passive Ultrasonic; Irrigation; Smear Layer